2003
DOI: 10.1038/sj.cgt.7700654
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-specific gene expression using regulatory elements of the glucose transporter isoform 1 gene

Abstract: In order to achieve tumor-specific targeting of adeno-associated virus (AAV)-mediated gene expression, the promoter of the glucose transporter isoform 1 (GLUT1) gene was cloned upstream of the enhanced green fluorescence protein (EGFP) and the herpes simplex virus thymidine kinase (HSVtk) gene. FACS analysis performed at 48 h after transient infection with rAAV/cytomegalovirus (CMV)egfp viral particles revealed an increase of fluorescence in all the cell lines tested. However, EGFP expression under control of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Previously, several cancer-specific promoters including the TERT (Gu et al, 2000;Gu and Fang, 2003), the synthetic hTERT promoter , tandem hypoxia-responsive elements (HRE) with the enhancerless SV40 promoter (Ruan et al, 2001), the alpha-fetoprotein promoter (Su et al, 1996), calcitonin gene regulatory sequence (Jiang et al, 2001) and the glucose transporter isoform 1 promoter (Sieger et al, 2004) have been identified and examined for cancer-specific expression. We tested the TERT promoter as naked plasmids in MCF7 and MDA-MB-231 cells, but the result showed weaker activation than those of both PRC1 and RRM2 promoters in the same transfection condition (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, several cancer-specific promoters including the TERT (Gu et al, 2000;Gu and Fang, 2003), the synthetic hTERT promoter , tandem hypoxia-responsive elements (HRE) with the enhancerless SV40 promoter (Ruan et al, 2001), the alpha-fetoprotein promoter (Su et al, 1996), calcitonin gene regulatory sequence (Jiang et al, 2001) and the glucose transporter isoform 1 promoter (Sieger et al, 2004) have been identified and examined for cancer-specific expression. We tested the TERT promoter as naked plasmids in MCF7 and MDA-MB-231 cells, but the result showed weaker activation than those of both PRC1 and RRM2 promoters in the same transfection condition (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Genes can be selectively delivered to tumors and their metastases with a range of vehicles (e.g., transferrin-coated polyethyleneimine complexes [13], genetically altered, Bretargetedâ denoviruses that express tumor-targeting protein sequences within their knobs, or bispecific antibodies that target antigens both on the tumor and on the delivery virus). Tumor-specific gene expression can be driven by tissue-or tumor-specific promoters, such as the PSA promoter in prostate carcinoma [14], the Chromogranin A promoter in neuroendocrine tumors [15], or the glut1 promoter, which is specific for many neoplastic tissues [16]. Weak tissue specific promoters can be amplified by using strategies such as the two-step transcriptional activation, or the CreYLoxP system [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The increase in GLUT1 transcription can be used for imaging or therapy by cloning a reporter gene or a therapeutic gene such as suicide genes downstream of the GLUT1 promoter/enhancer elements (Haberkorn et al 2002. Examples are the herpes simplex virus thymidine kinase (HSVtk) gene or the sodium iodide symporter, where adeno associated virus or retroviral vectors have been used to transfect tumor cells and to measure the uptake of specific substrates or to treat animals with genetically modified tumors (Sieger et al 2003(Sieger et al , 2004. In these studies, reporter gene expression (green fluorescent protein, HSVtk or sodium iodide symporter) was specific for tumor cells or cells with expression of an activated ras oncogene (Fig.…”
Section: Glucose Metabolismmentioning
confidence: 99%